2015
DOI: 10.1002/smll.201500607
|View full text |Cite
|
Sign up to set email alerts
|

Light or Heat? The Origin of Cargo Release from Nanoimpeller Particles Containing Upconversion Nanocrystals under IR Irradiation

Abstract: Nanoimpellers are mesoporous silica nanoparticles that contain azobenzene derivatives bonded inside the pores and rely on the continuous photoisomerization of multiple azobenzenes to release cargo under near UV irradiation. A recent study employs upconversion nanocrystal embedded particles to replace UV light with IR light to stimulate nanoimpellers. However, the photothermal effect of IR irradiation and its likely contribution to the observed release behavior are not examined. It is found that, in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…The study did report the light‐triggered power‐dependent release of cargo in solution and in cells, however, the heat contribution was not investigated. Dong and Zink investigated the light and heat contributions to account for the cargo release from UpconversionNP@mesoporous organosilica nanoimpellers ( Figure a) . They found that control experiments using mesoporous organosilica nanoimpellers without upconverting core released their content both with a 403 nm (where azobenzenes absorb) and a 980 nm irradiation (where azobenzenes do not absorb), which implied that the heat contribution can be significant in the NIR.…”
Section: Cargo Loading and Delivery Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study did report the light‐triggered power‐dependent release of cargo in solution and in cells, however, the heat contribution was not investigated. Dong and Zink investigated the light and heat contributions to account for the cargo release from UpconversionNP@mesoporous organosilica nanoimpellers ( Figure a) . They found that control experiments using mesoporous organosilica nanoimpellers without upconverting core released their content both with a 403 nm (where azobenzenes absorb) and a 980 nm irradiation (where azobenzenes do not absorb), which implied that the heat contribution can be significant in the NIR.…”
Section: Cargo Loading and Delivery Strategiesmentioning
confidence: 99%
“…Temperature–time profile of the UpconversionNP@MON under NIR actuation b). Reproduced with permission …”
Section: Cargo Loading and Delivery Strategiesmentioning
confidence: 99%
“…The reversible photoisomerization caused by the simultaneous emission of UV/blue light from the UCNPs and the photothermal effect of 980 nm light creates acontinuous rotationinversion movement, which can be used to trigger the release of the encapsulated chemotherapy drug. [10] Independently,the PDT can also be realized under the stimulus of green emission excited by 796 nm under high power density (> 0.5 Wcm À2 ). Rose Bengal (RB) was used as the photosensitizing molecule Figure 4G)shows that the viability of cells is maintained at more than 80 %e ven at ah igh concentration (ca.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In this nanocomposite,t he NIR DCL under low power density 796 nm (< 0.5 Wcm À2 )e xcitation is used as abioimaging signal ( Figure 4B), the green-emissiontriggered photodynamic therapy (PDT) cannot work under these conditions.H owever,t hrough the consistency between the UV/blue emission and the absorption of the light sensitive azobenzene (Azo) nanoimpeller (the transformation between the cis-isomer and trans-isomer of Azo can work like ai mpeller to drive the release of guest) ( Figure 4D), [9] Tm 3+ dominated UV/blue emission under 980 nm excitation could be used to trigger the release of the chemotherapy drug. [10] Independently,the PDT can also be realized under the stimulus of green emission excited by 796 nm under high power density (> 0.5 Wcm À2 ). [10] Independently,the PDT can also be realized under the stimulus of green emission excited by 796 nm under high power density (> 0.5 Wcm À2 ).…”
Section: Lanthanide-doped Upconversion Nanoparticles (Ucnps)mentioning
confidence: 99%